PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA ALOKASI UMUM (DAU), DAN DANA ALOKAI KHUSUS (DAK) TERHADAP PERTUMBUHAN EKONOMI SEBELUM DAN SAAT TERJADI PANDEMI (PADA PROVINSI KALIMANTAN TENGAH PERIODE 2018 - 2021) - Edi Sudiarto; Lidia Andiani; Lusiana Lusiana; Jayana Salesti (MEASUREMENT : Jurnal Program Studi Akuntansi, 2022)
Economic growth of a region has a major effect on economic welfare for both the central government and regional governments. The data used in this study is data taken before and during the 2018-2021 pandemic. By using a cluster sampling technique consisting of 14 districts as a sample, the number of samples processed is 56 samples. The method in this study uses quantitative data, the data is tested using classical assumptions, hypotheses (F, R² t), multiple linear regression analysis with assistance tools SPSS 22. The results of this study are Economic Growth, Local Own Revenue (PAD), General Allocation Fund (DAU), and Special Allocation Fund (DAK)  Positive Effects on Economic Growth 2018-2021.